Realizing Sustainable Sharia Banking Governance: An Analysis Of The Implementation Of Good Corporate Governance And Shariah Governance In Indonesian Sharia Banks - Nur Khusnia; Mugiyati Mugiyati; Auwwalu Shuaibu Muhammad; Nurul Suhada Ismail (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
Good Islamic banking governance is the main foundation for maintaining stability and trust in the Islamic financial industry. Bank Syariah Indonesia (BSI), as the largest Islamic bank in Indonesia, has a strategic role in effectively implementing the principles of Good Corporate Governance (GCG) and Sharia Governance. This study aims to analyze the implementation of GCG and Sharia Governance at BSI based on the latest data from 2024. The method used is qualitative descriptive analysis with a literature review approach and secondary data from BSI's GCG implementation reports. The results of the study indicate that although BSI has received various recognitions related to good corporate governance practices, challenges in the aspects of Sharia Supervisory Board independence, financial transparency, and compliance with Sharia principles remain key concerns. Therefore, strengthening internal oversight systems, enhancing information transparency, and improving Sharia compliance are necessary to maintain stakeholder trust and promote sustainable growth in Sharia banking.